Insights Into the Emerging Role of Baf53b in Autism Spectrum Disorder - Rowland, Megan E.; Jajarmi, Jana M.; Osborne, Tess S. M.; Ciernia, Annie Vogel (Frontiers in Molecular Neuroscience, 2022)
Accurate and precise regulation of gene expression is necessary to ensure proper brain development and plasticity across the lifespan. As an ATP-dependent chromatin-remodeling complex, the BAF (Brg1 Associated Factor) complex can alter histone-DNA interactions, facilitating dynamic changes in gene expression by controlling DNA accessibility to the transcriptional machinery. Mutations in 12 of the potential 29 subunit genes that compose the BAF nucleosome remodeling complex have been identified in several developmental disorders including Autism spectrum disorders (ASD) and intellectual disability. A novel, neuronal version of BAF (nBAF) has emerged as promising candidate as its expression is tied to neuron differentiation and it’s hypothesized to coordinate expression of synaptic genes across brain development. Recently, mutations in BAF53B, one of the neuron specific subunits of the nBAF complex, have been identified in patients with ASD and Developmental and epileptic encephalopathy-76 (DEE76), indicating BAF53B is essential for proper brain development. Recent work in cultured neurons derived from patients with BAF53B mutations suggests links between loss of nBAF function and neuronal dendritic spine formation. Deletion of one or both copies of mouse Baf53b disrupts dendritic spine development, alters actin dynamics and results in fewer synapses in vitro. In the mouse, heterozygous loss of Baf53b severely impacts synaptic plasticity and long-term memory that is reversible with reintroduction of Baf53b or manipulations of the synaptic plasticity machinery. Furthermore, surviving Baf53b-null mice display ASD-related behaviors, including social impairments and repetitive behaviors. This review summarizes the emerging evidence linking deleterious variants of BAF53B identified in human neurodevelopmental disorders to abnormal transcriptional regulation that produces aberrant synapse development and behavior.